2020
DOI: 10.1111/febs.15256
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis (ASHH2) CW domain binds monomethylated K4 of the histone H3 tail through conformational selection

Abstract: Chromatin post-translational modifications are thought to be important for epigenetic effects on gene expression. Methylation of histone N-terminal tail lysine residues constitutes one of many such modifications, executed by families of histone lysine methyltransferase (HKMTase). One such protein is ASHH2 from the flowering plant Arabidopsis thaliana, equipped with the interaction domain, CW, and the HKMTase domain, SET. The CW domain of ASHH2 is a selective binder of monomethylation at lysine 4 on histone H3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 64 publications
4
21
0
Order By: Relevance
“…This observation is in line with the flexible nature of ASHH2 CW and the proposed mechanism of conformational selection [24]. The most notable changes in chemical shifts are found in the first β-strand, perhaps related to the nascent β-sheet augmentation discussed in [24], in the conserved W891 that is not part of the binding pocket, in the ɑ1-helix and the η1-loop (Fig. 2A).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…This observation is in line with the flexible nature of ASHH2 CW and the proposed mechanism of conformational selection [24]. The most notable changes in chemical shifts are found in the first β-strand, perhaps related to the nascent β-sheet augmentation discussed in [24], in the conserved W891 that is not part of the binding pocket, in the ɑ1-helix and the η1-loop (Fig. 2A).…”
Section: Resultssupporting
confidence: 79%
“…Recent X-ray (Liu et al, PDB code: 5YVX) ) and NMR (Dobrovolska et al, PDB code: 6QXZ) structural studies described the CW of ASHH2 in complex with H3K4me1. The published structures agreed on the core of the complex; however, the structural data related to the 1-helix and the following C-terminal regions differ [23,24]. The studies also concluded differently with respect to binding mechanisms and determinants.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations